"Where is our Steve Jobs?" A case study of consumerism and neo-liberal media in China. (November 2014) - Liu, Zhengjia; Berkowitz, Dan
When covering foreign events, journalists bring resonant cultural meanings to an otherwise little-understood occurrence. From a cultural perspective, we analyzed "Steve Jobs fever" in five publications of a progressive neo-liberal media group in China. The media texts allowed us to understand society's neo-liberal narratives. The media re-crafted Jobs' death into a story about Chinese society: the first theme foreshadowed the greatness and necessity of having Steve-Jobs-style genius; the second theme raised the question why not having an equivalent Steve Jobs and immediately answered it; finally, the third theme logically provided the solution to solve this social crisis. This story fits into the enduring narratives of national salvation through technological consumption and further Westernized liberalization. The study attempts to move research on Chinese media beyond the Chinese context by making a conceptual contribution for understanding journalism in a global environment.